REFLECTION OF WOMEN'S SPIRITUALITY AND SPIRITUAL WORLD IN LITERATURE (Scientific journal of the Fergana State University, 2026)
This article examines the reflection of women’s fate and psyche in fictional stories. It also emphasizes that, in literary studies, analyzing the psyche and fate of women is considered one of the central characteristics of fiction.